Malnutrition rate among hospitalized patients with type 2 diabetes mellitus - Gul Yildirim, Zeynep; Uzunlulu, Mehmet; Telci Caklili, Ozge; Mutlu, Hasan Huseyin; Oguz, Aytekin (Progress in Nutrition, 2018)
Aim: Rate of obesity is high among patients with type 2 diabetes thus assessment of the nutritional status is often ignored in these patients. This study aimed to evaluate nutritional status of patients with type 2 diabetes mellitus who were hospitalized forpoor glycemic control and to define the risk factors related to malnutrition. Methods: Study included a total of 104 patients (67 female, 37 male, mean age: 65.08±12.57) who were hospitalized in the Internal Medicine Clinics for poor glycemic control. Patients’ nutritional status was evaluated on the first day of admission. Demographic, anthropometric and biochemical data of the cases were evaluated. Nutritional status was assessed with Mini Nutritional Assessment(MNA) test. Results: Malnutrition rate was 7.7%, rate of the patients with malnutrition risk was 18.3% and rate of the patients with normal nutritional status was found as 74%. Body mass index was 25 kg/m2or higher in 37.5% of the patients with malnutrition and 63.2% in patients with malnutrition risk. In logistic regression analysis, duration of diabetes [(between 15-20 years OR: 5.535 (95% CI:1.15-26.61), >20 years OR: 7.147 (95% CI:1.59-31.96)] and BMI[<25 kg/m2 OR: 4.565 (95% CI:1.47-14.13)] were the independent risk factors correlated with malnutrition. Conclusions: One in every four patients with type 2 diabetes hospitalized due to poor glycemic control was observed to have malnutrition or have malnutrition risk indicating nutritional assessment should be performed in hospitalized patients with type 2 diabetes even if they are overweight or obese.